2021
DOI: 10.1016/j.rbmo.2021.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus cells of euploid versus whole chromosome 21 aneuploid embryos reveal differentially expressed genes

Abstract: Research Question: Can cumulus cells be employed as a non-invasive target for the study of determinants of preimplantation embryo quality? Design: Cumulus cells were collected from Monosomy 21, Trisomy 21 and Euploid embryos and subjected to RNA sequencing analysis and Real Time PCR assays. The differential gene expression was analyzed for different comparisons. Result(s): A total of 3122 genes in Monosomy 21 CCs, and 19 genes in Trisomy 21 CCs were differentially expressed compared to euploid CCs. Thirteen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…They interact directly with the oocyte to facilitate its maturation and are bathed in the same FF. Some studies identified differences regarding few markers of oxidative stress [61] or gene expression between euploid and aneuploid oocytes [62]. FF is also collected during oocyte retrieval.…”
Section: Ffs and Cumulus Cellsmentioning
confidence: 99%
“…They interact directly with the oocyte to facilitate its maturation and are bathed in the same FF. Some studies identified differences regarding few markers of oxidative stress [61] or gene expression between euploid and aneuploid oocytes [62]. FF is also collected during oocyte retrieval.…”
Section: Ffs and Cumulus Cellsmentioning
confidence: 99%